Highly Selective Solid‐Phase Extraction of Pb(II) by Ion‐Imprinted Superparamagnetic Mesoporous Silica. Issue 1 (7th January 2019) - Shah, Syed Mazhar; Su, Xingguang; Muhammad, Faheem; Traore, Zoumana Sékou; Gao, Yuan
Abstract: Pb (II)‐imprinted superparamagnetic mesoporous silica (SPMS) adsorbent has been synthesized and characterized. The thiol functionalized SPMS offered a fast adsorption kinetics for Pb(II) and equilibrium was achieved in just 20 min at pH 8.0. The adsorption isotherm data fits well with Langmuir model with a maximum adsorption capacity of 377.36 mg g −1 . The selectivity co‐efficients of imprinted adsorbent for Pb(II)/Cu(II) and Pb(II)/Bi(III) were 3.36 and 3.05 times higher than that of non‐imprinted adsorbent. The imprinted adsorbent was employed for the solid phase extraction of Pb(II) and its detection by graphite furnace atomic absorption spectrometry (GFAAS).The parameters affecting the determination of Pb(II) were also well investigated and optimized. A linear relationship between the Pb(II) concentration and the absorbance was found in the range of 0.8‐500 ng mL −1 with a detection limit of 0.25 ng mL −1 . The imprinted adsorbent was applied to the determination of Pb(II) in two certified sediment samples with satisfactory results, which indicates that Pb(II)‐imprinted superparamagnetic mesoporous silica adsorbent possess promising features of a viable adsorbent for the preconcentration of Pb(II) ions in complex matrices. Abstract : A highly selective ion‐imprinted mesoporous silica sorbent has been prepared for extraction and preconcentration of Pb(II) from sediments. The specific recognition sites on the sorbent acted a lock and key system and increased its selectivity for Pb(II) over other co‐existing ions. The imprinted sorbent achieved faster adsorption and exhibited higher adsorption capacity as compared to its non‐imprinted analogue.